2011
DOI: 10.1186/1471-2164-12-546
|View full text |Cite
|
Sign up to set email alerts
|

Functional microRNA screening using a comprehensive lentiviral human microRNA expression library

Abstract: BackgroundMicroRNAs (miRNAs) are a class of small regulatory RNAs that target sequences in messenger RNAs (mRNAs) to inhibit their protein output. Dissecting the complexities of miRNA function continues to prove challenging as miRNAs are predicted to have thousands of targets, and mRNAs can be targeted by dozens of miRNAs.ResultsTo systematically address biological function of miRNAs, we constructed and validated a lentiviral miRNA expression library containing 660 currently annotated and 422 candidate human m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 55 publications
1
21
0
Order By: Relevance
“…In contrast, decreasing the availability of miR-135s further inhibits RGC axon regeneration. The developmental and regeneration-promoting effects of miR-135s both rely in part on silencing of KLF4, a well known intrinsic inhibitor of axon regeneration (Moore et al, 2009;Qin et al, 2013). Together, these data identify novel neuronal functions for miR-135s and highlight the potential of applying miRNAs to injured CNS neurons as an approach for facilitating CNS axon regeneration.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…In contrast, decreasing the availability of miR-135s further inhibits RGC axon regeneration. The developmental and regeneration-promoting effects of miR-135s both rely in part on silencing of KLF4, a well known intrinsic inhibitor of axon regeneration (Moore et al, 2009;Qin et al, 2013). Together, these data identify novel neuronal functions for miR-135s and highlight the potential of applying miRNAs to injured CNS neurons as an approach for facilitating CNS axon regeneration.…”
Section: Introductionmentioning
confidence: 88%
“…However, for many of these targets (e.g., PTK2, TAF4), knock-down had been reported to reduce neurite growth or neuron migration (data not shown). KLF4 was particularly interesting because knock-down of KLF4 in neurons, similar to overexpression of miR-135s, enhances axon growth, leading process length, and neuronal migration (Moore et al, 2009;Qin and Zhang, 2012). Furthermore, recent work in vascular smooth muscle and hepatocellular carcinoma cells links miRNA-135a to KLF4 (Lin et al, 2016;Yao et al, 2016).…”
Section: Mir-135a and Mir-135b Control Axon Growth And Neuronal Migramentioning
confidence: 99%
“…For example, the barcode of a miR whose overexpression inhibits cell growth would decrease over time; Izumiya et al identified candidate pancreatic cancer suppressive miRs on this basis (22). Conversely, by determining barcodes enriched in migrated cells vs. the starting cell population, candidate miRs that promoted invasiveness of cancer cell lines were identified (23,26). Although these studies successfully employed pooled viral miR libraries in functional screens, their viral miR barcode quantification methods required custom-made microarrays (22,24), bead-based detection systems (20,21) or high-throughput sequencing (23,26).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, by determining barcodes enriched in migrated cells vs. the starting cell population, candidate miRs that promoted invasiveness of cancer cell lines were identified (23,26). Although these studies successfully employed pooled viral miR libraries in functional screens, their viral miR barcode quantification methods required custom-made microarrays (22,24), bead-based detection systems (20,21) or high-throughput sequencing (23,26). Those approaches require access to costly high-throughput infrastructure and sophisticated informatics analyses, thus restricting the accessibility of these assays.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in vitro screens based on miRNA expression libraries have proven highly useful (Voorhoeve et al, 2006; Izumiya et al, 2010; Huang et al, 2008; Poell et al, 2011). For instance, miR-372/373 were found to be potent oncogenes that have a stronger effect than p53 knockdown in relieving oncogene-induced senescence (Voorhoeve et al, 2006).…”
Section: Introductionmentioning
confidence: 99%